Carcross, Yukon Territory, approximately 1898. - Hegg, Eric A., 1867-1948 (1898)
Shows two men, one a North-West Mounted Police officer, in a boat. Carcross was located at the junction of Bennett Lake and Tagish Lake. Caption on image: "Cariboo Crossing, Y.T." Original photograph by Eric A. Hegg 730; copied by Webster and Stevens 64.A.